2000
DOI: 10.2307/3454294
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality and Reproductive Endocrine Function in Relation to Biomarkers of Lead, Cadmium, Zinc, and Copper in Men

Abstract: Blood lead (BPb), actity of 6-aminolevulinic add dehydratase (ALAD), erythrocyte protoporphyrin (EP), blood cadmium (BCd), serum zinc (SZn), seminal fluid zinc (SaZn), serum copper (SCu), and parameters of semen quality and of reproductive endocrine function were measured in 149 healthy male industrial workers 20-43 years of age. The group contained 98 subjects with slight to moderate occupational exposure to Pb and 51 reference subjects. All of the subjects lived in Zagreb, Croatia. Significant (p < 0.05) cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
5
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(138 citation statements)
references
References 0 publications
4
120
5
9
Order By: Relevance
“…Several studies have reported declines in semen quality associated with both Pb [4,11,13] and Cd concentrations in blood [10,14]. However, we observed no significant associations between blood levels of heavy metals and any semen parameters.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Several studies have reported declines in semen quality associated with both Pb [4,11,13] and Cd concentrations in blood [10,14]. However, we observed no significant associations between blood levels of heavy metals and any semen parameters.…”
Section: Discussioncontrasting
confidence: 83%
“…Human, animal and in vitro studies suggest that heavy metals may have adverse impacts on male reproductive health [1-10], even at relatively low-level exposures [11]. Heavy metals could adversely affect the male reproductive system, either by causing hypothalamic-pituitary axis disruption or by directly affecting spermatogenesis, resulting in impair semen quality [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heavy metals Cadmium Clough et al, 1990Janecki et al, 1992Clough et al, 1990Hew et al, 1993Wong et al, 2004El-Demerdash et al, 2004Foote 1999;Pant et al, 2003;Telisman et al, 2000;Tvrdá et al, 2013Mercury Monsees et al, 2000-Monsees et al, 2000Keck et al, 1993Keck et al, 1993Lead Batarseh et al, 1986Adhikari et al, 2000Batarseh et al, 1986Bizarro et al, 2003Alexaki et al, 1990Hsu et al, 1997;Huang et al, 2001;Kasperczyk et al, 2008;Shafai et al, 2011 Chemicals continuously exposed and/or subjected to high concentrations, which may cause health problems, including sub...…”
Section: Sperm Parametersmentioning
confidence: 99%